Areas at risk of flooding in Wadi Bisha basin in KSA - Alshamrani, Nada Saad; Madani, Ferdous Mohammed (Journal of natural sciences, life and applied sciences, 2022)
The Wadi Bishah watershed is located in the southwestern of Asir province in Saudi Arabia, it’s characterized by hydromorphometric properties that control the water resources. The study aimed to identify the morphometric properties of this watershed and the drainage network, and the hydrological characteristics that affect the occurrence of floods. Some modern methods were used such as: (GIS, statistical method, cartography) to identify flood area. The study found that the region’s hydrological resources contributed to a water surplus in the Wadi Bishah; This leads to occasionally flood risks under geological, topography, hydrological… controls, and local water storage in King Fahd Dam. The most hazardous sub-basins in the occurrence of floods in Bishah watershed were identified; They are the principal Bishah river and the Rania River. The study also made some recommendations regarding the management of surface water resources to prevent flood hazards and the use of GIS techniques in the early warning and water harvesting operations in the Bishah river.